Chronic pain in the Chilean population: risk factors prevalence and cognitive associations - Hernández, Hernán; Ochoa-Rosales, Carolina; Ibáñez, Agustín; Oyanadel, Lorena; Olavarria, Loreto; Marín-Díaz, Nickole; Caviedes, Ariel; Hazelton, Jessica L.; Ramos, Teresita; Santamaria-García, Hernando; Custodio, Nilton; Montesinos, Rosa; et al. (Frontiers in Aging, 2025)
Chronic pain (CP) is a global public health issue and a critical factor in the aging process. Chile, as one of the most aged countries in Latin America, presents a unique context for exploring CP and its associated factors. Despite its significance in aging, previous studies in the region often fail to comprehensively address key variables such as age, income, mood, mobility, diet, and cognitive skills, nor do they systematically investigate the relationship between CP and cognitive impairment. This study presents a comprehensive analysis of CP prevalence, related sociodemographic and health variables, and its link to cognitive impairment, using representative data of the Chilean population 15 years and older from the 2009–2010 and 2016–2017 Chilean National Health Surveys (CNHS). In the expanded sample of 12,791,542 and 13,399,937 individuals respectively, the overall prevalence of CP was 46.0% in the 2009–2010 CNHS and 28.9% in the 2016–2017 CNHS, with prevalence increasing with age. CP ranged from 26.6% among individuals aged 15–24 years to 59.9% among those aged 65–80 years in the 2009–2010 CNHS, and from 16.6% to 40.2% in the 2016–2017 CNHS. Female participants consistently reported higher CP rates, with significantly higher prevalence than males across age groups 15–64 years. Using complex survey logistic regression analyses, we identified several factors that were significantly associated with CP, including reduced mobility, depression, anxiety, socioeconomic disadvantage, and lower educational attainment. Machine learning techniques were employed to classify CP and non-CP cases, providing a nuanced understanding of the complex interplay between factors that influence CP. In a secondary analysis among those 60 years and older, no significant difference in CP prevalence was observed between individuals with and without cognitive impairment measured with an abbreviated MiniMental State Examination test. However, those with cognitive impairment tended to report pain in a greater number of anatomical sites. This study provides the first nationally representative evidence of CP in Chile in relation to age, income, mood, mobility, diet, and cognitive performance. These findings contribute to the understanding of CP as a public health issue in Latin America. The study underscores the need for targeted interventions to promote healthy longevity and reduce the burden of chronic diseases in aging populations.